Analisis Investasi Saham dalam Sistem Hukum Ekonomi Syariah: Sebuah Syarah Hadis Pendekatan Isu Kontemporer - Sholihat, Novi Nur (Jurnal Riset Agama, 2022)
This study aims to analyze the hadith about stock investment in Islam. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of this study found that the quality status of the investment hadith was assessed as hasan li ghairihi, in the sense of maqbul and ma'mul bih for Muslim practice. The conclusion of this study is that the hadith of the Prophet Muhammad regarding stock investment in Islam is a recommended activity, because investment activities have been carried out by the Prophet Muhammad since he was young until before the apostleship. Unless prohibited activities are found in investment activities, both objects and procedures, the investment is prohibited. This study recommends that further research be carried out through collaboration between enthusiasts of hadith science and business economics to research related to stock investment in terms of objects and processes if you want to invest in stocks in accordance with Islamic teachings.